Role of thioredoxin-interacting protein in diseases and its therapeutic outlook - Qayyum, Naila; Haseeb, Muhammad; Kim, Moon Suk; Choi, Sangdun (International Journal of Molecular Sciences, 2021)
Thioredoxin-interacting protein (TXNIP), widely known as thioredoxin-binding protein 2 (TBP2), is a major binding mediator in the thioredoxin (TXN) antioxidant system, which involves a reduction-oxidation (redox) signaling complex and is pivotal for the pathophysiology of some dis-eases. TXNIP increases reactive oxygen species production and oxidative stress and thereby contributes to apoptosis. Recent studies indicate an evolving role of TXNIP in the pathogenesis of complex diseases such as metabolic disorders, neurological disorders, and inflammatory illnesses. In addition, TXNIP has gained significant attention due to its wide range of functions in energy me-tabolism, insulin sensitivity, improved insulin secretion, and also in the regulation of glucose and tumor suppressor activities in various cancers. This review aims to highlight the roles of TXNIP in the field of diabetology, neurodegenerative diseases, and inflammation. TXNIP is found to be a promising novel therapeutic target in the current review, not only in the aforementioned diseases but also in prolonged microvascular and macrovascular diseases. Therefore, TXNIP inhibitors hold promise for preventing the growing incidence of complications in relevant diseases.
Keywords: Animals; Carrier Proteins; Humans; Inflammation; Metabolic Syndrome; Neoplasms; Nervous System Diseases; Nuclear Proteins; Reactive Oxygen Species; TATA Box Binding Protein-Like Proteins; Thioredoxins; Tumor Suppressor Proteins; Metabolic disorders; Neurological disorders; Thioredoxin; TXNIP; TXNIP modulator